OPTIMALISASI PESONA HERBAL SEBAGAI UPAYA KEMANDIRIAN DAN KETAHANAN PANGAN RUMAH TANGGA - Mustofa2), IGP Suryadarma1), Asri Widowati1), (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
The activity "Optimizing of The Beauty of Herbs" is aimed: (1) toimprove an understanding of the understanding of farmer group membersand efficacy of herbs scientifically; (2) to improve the creativity of membersof farmer groups on how the processing of various herbal products, (3)toimprove awareness of farmer group members to be independent andmaintain the food security.Objects of study are 45 member of farmer group " Sumber KaryaBoga " in Padukuhan Pondok, Condong Catur. The methods are used insolving the problem include: lecture, workshop and practice. Stages include:the preparation stage, the introduction stage, the creative production stage,development stage and evaluation stage. Data obtained using a questionnaireabout herbs and their understanding of the sources of information, selfsufficiency,food security, entrepreneurial spirit and understanding of thebusiness plan .Results indicate that most participants have an understanding ofherbs and their properties well. Participants also gain the skills to processherbs into various food products . The independence of most participantshas reached "Good" category. For food security and entrepreneurial spiritobtained information that most participants have food security in thecategory "Good". But only few of them know about farming business plan.This suggests that they have not yet fully understand about the formulationof business plan.Keywords: the beauty of herb, food security, and enterpreneurship